Etnomodelagem: modelagem matemática no interior de uma comunidade rural sustentável - Martins, Rafael Bida Guabiraba (Universidade Federal de São Carlos, 2020)
Based on the assumption that Ethnomodelling is grounded on the process of reflection of the routine of a single individual or an entire community, that is not academic, this would be defended as analysis and study of local knowledge present in different groups, linked to the social construction of a specific people, where one of the assumptions of this would be the study of local knowledge developed by members of this community. Based on this idea, the research aims to discuss how possible ethnomodeling an identification of knowledge present in the models built in a rural community, as well as problematize the hegemonic scientific discourse institutionalized by mathematics academic. This study was taked root using an ethnographic approach, when interacting with individuals belonging to a farming community who work with organic food production in the municipality of São Carlos, state of São Paulo. It was possible to make a connection of each aspect cultural issues, such as the elaboration of problems and questions that are retired of the systems that are part of the reality of those present in this culture, considering that academic mathematics is not the only way to identify a probable knowledge, neither in the study of different undestandings, but dealt with the valorization of all forms of knowledge. In essence, the process of Modeling does not have the interest of working from a perspective of which knowledge is right or wrong, it is valid or neutral, but it is beyond a message transmission of hegemonic knowledge, those that have been used today considered as knowledge accumulated by humanity, making possible thus an insurrection of other sabers.
Ethnomodeling: mathematical modeling inside a sustainable rural community
Keywords: Etnomatemática; Insurreição de saberes; Linguagem Matemática; Comunidade CSA; Ethnomathematics; Mathematical modeling; Insurrection of knowledge; Mathematical language; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM